Pemanfaatan Media Baru dalam Penyebaran Informasi Publik melalui YouTube Radio Republik Indonesia Kota Bogor - Salimah Renata Ghassani; Hudi Santoso (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines how Radio Republik Indonesia (RRI) Bogor City uses YouTube to disseminate public information in an increasingly digital media landscape. A qualitative descriptive approach was adopted, with informants selected through purposive sampling; data were gathered via interviews, observation, documentation, and direct field participation. Results show that the channel carries informational, educational, and institutional content in audiovisual form. According to YouTube Analytics, the Podcast Ruang Suara playlist led all playlists at 71% of total playlist performance, and the channel drew roughly 1,800 unique users each month. Content is managed across four stages — planning, production, publication, and evaluation — yet two persistent problems undercut the operation: a shortage of dedicated personnel and irregular upload schedules. These findings suggest that YouTube holds real strategic value for RRI Bogor City's public information mandate, provided the institution commits to steadier, more purposeful content management going forward.